Weather context in the Vietnamese Mekong Delta under the impacts of the typical ENSO phases - Hoang, T. V. H.; Dang, T. A. (MAUSAM, 2025)
The shifting season features of precipitation due to the El-Niño and La-Nina events, under the impacts of global climate change (GCC), have increased the potential risks of crop yield decline in rice cultivation areas (CCAs) worldwide. This study examines the relationship between the typical El-Niño and La-Nina phases and the season features of precipitation, and their subsequent impact on CCAs within the Vietnamese Mekong Delta (VMD). Daily rainfall data from 12 observation stations from 1986 to 2022 were analyzed to investigate the connection between ENSO events and season features across the VMD. The results indicate that the El-Niño and La-Nina events significantly influence the timing and duration of season features in the VMD. During the La-Niña event in the period 1999-2001, the rainy season onset date (RSOD) and rainy season cessation date (RSCD) occurred three weeks earlier and two weeks later, respectively, than the long-term average (1986-2022). Conversely, during the extreme El-Niño event of the stage 2014-2026, the RSOD and RSCD were delayed, occurring 10.9 and 5.0 days later than the long-term average, with a shorter length of rainy season (LRS) by 5.9 days over the entire VMD. These shifts in the season features of precipitation under the GCC have impacted cultivation activities in the VMD. The findings underscore the vulnerability of rice cultivation regions in the VMD to ENSO-driven climate variability, emphasizing the importance of proactively implementing adaptation solutions to mitigate the negative impacts of GCC.